2023
DOI: 10.1007/s00482-023-00756-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific results of the Dresden children and adolescents headache program DreKiP

Laura Zaranek,
Hanna Sobe,
Matthias Richter
et al.

Abstract: Zusammenfassung Hintergrund Mädchen und Frauen sind häufiger von Kopfschmerzen betroffen als Jungen und Männer. Der Einfluss des Geschlechts auf die Wirksamkeit von Kopfschmerztherapien ist bisher kaum untersucht. Wir prüften geschlechterspezifische Unterschiede im ambulanten multimodalen Dresdner Kinder- und Jugendkopfschmerzprogramm DreKiP. Methoden 140 Patienten mit primären Kopfschmerzen wurden in einem 15-stündigen strukturiertem Gruppen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Among 5,944 adolescents (50.7% boys and 49.3% girls), being female was associated with an increased risk of having a headache in Turkey ( 7 ). Girls also showed a significantly higher headache frequency than boys among adolescents in Germany ( 10 ), Indonesia ( 11 ), Lithuania (except tension headache) ( 16 ), and Brazil ( 15 ). On the other hand, no such association was observed with gender among Canadian adolescents ( 14 ), and only a weak association was reported between migraine, tension headache, and female gender among adolescents in Zambia ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 5,944 adolescents (50.7% boys and 49.3% girls), being female was associated with an increased risk of having a headache in Turkey ( 7 ). Girls also showed a significantly higher headache frequency than boys among adolescents in Germany ( 10 ), Indonesia ( 11 ), Lithuania (except tension headache) ( 16 ), and Brazil ( 15 ). On the other hand, no such association was observed with gender among Canadian adolescents ( 14 ), and only a weak association was reported between migraine, tension headache, and female gender among adolescents in Zambia ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that headache is the leading reported cause of school absenteeism among children and adolescents ( 7 ). Although the exact etiology of primary headache disorders among adolescents is not yet fully understood ( 8 ), several factors, such as age ( 7 , 9 ), sex ( 4 , 10 , 11 ), obesity, underweight ( 12 ), anxiety/depression ( 11 , 13 , 14 ), and sleep disorders ( 11 , 15 ) are associated with primary headache disorders among children and adolescents. Recent reports show varied primary headache disorders rates among adolescents in different countries ( 3 , 7 , 9 11 , 16 ).…”
Section: Introductionmentioning
confidence: 99%